Food insecurity in Southern Africa :causes and emerging response options from evidence at regional, provincial and local scales - Misselhorn, Alison Anne (My University, 2007)
The overarching objective of this thesis is to determine causes of food insecurity in southern Africa, and how it can best be addressed. This objective is addressed through a number of research questions and methods at three geographic scales: the regional, through a technique of meta-analysis which is used to synthesise 49 local-level household economy case studies; the provincial, through a Delphi panel of practitioner experience; and the local, using multiple research techniques, including participatory methods. An extremely diverse range of factors contributing to food-insecurity are found at all three scales, indicating that community- and household-specific dynamics give rise to forms of food insecurity. Two common processes, however, are argued to be common across all the casestudy communities in the regional-scale research. These are the closely related processes of cycles of intensifying vulnerability associated with livelihood ‘trade-offs’, and of communitylevel social capital changing into forms that undermine resilience to food insecurity - such as the decline in two-parent families. A further probing of social capital at the local level suggests that while social capital takes multiple forms, and further remains in many respects a problematic concept, it nevertheless provides a valuable lens through which powerful social dynamics might be examined in developing responses to food insecurity. Policy makers and change agents should carefully consider their role in building community social-capital that might enhance the ability of vulnerable communities to overcome livelihood constraints and adapt to the tremendous challenges posed by changing economic environments in southern Africa. Drawing on the research at all scales, a framework is provided that calls for a reconceptualisation of food-security interventions to focus on intervention processes, applicable at all scales and in all contexts across the region. The development of social capital, participation, co-ordination and learning interactions are explored as central elements in these processes. The framework asks for closer attention to both the appropriate mechanisms (such as policy) necessary to effect change, and the human dimensions that give these mechanisms agency. The findings of the thesis represent an additional shift in understanding food security to acknowledge that the value of a political economic interpretation of food security is limited independent of an understanding of the cross-scale social networks and relational interactions that ultimately configure and reconfigure it.
Student Number : 0206926T - PhD thesis - School of Geography, Archaeology and Environmental Studies - Faculty of Science
Keywords: food security; social capital; vulnerabilty; food security interventions